2019
DOI: 10.1038/s41598-019-45155-6
|View full text |Cite
|
Sign up to set email alerts
|

miR-29c overexpression and COL4A1 downregulation in infertile human endometrium reduces endometrial epithelial cell adhesive capacity in vitro implying roles in receptivity

Abstract: The endometrium is a highly complex tissue that is vulnerable to subtle gene expression changes and is the first point of contact for an implanting blastocyst. Successful blastocyst implantation can only occur when the endometrium is receptive during a short window with each menstrual cycle. microRNAs are small, non-coding RNAs that negatively regulate their gene targets. miR-29c has previously been identified to be differentially regulated across the fertile menstrual cycle, however it has not been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…COL4A1 downregulation in infertile human endometrium reduces endometrial epithelial cell adhesive capacity [18], which implied COL4A1 expression can inhibit primary tumor segregation and result in metastasis. Several types of collagen have been identified to process antiangiogenic domains that can be released by proteolysis of the basement membrane (BM), a specialized form of the extracellular matrix [19,20], and COL4A1 is a major transcriptional target of p53 [11]. We found COL4A1 expression contributed to the better prognosis in BC patients who received neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…COL4A1 downregulation in infertile human endometrium reduces endometrial epithelial cell adhesive capacity [18], which implied COL4A1 expression can inhibit primary tumor segregation and result in metastasis. Several types of collagen have been identified to process antiangiogenic domains that can be released by proteolysis of the basement membrane (BM), a specialized form of the extracellular matrix [19,20], and COL4A1 is a major transcriptional target of p53 [11]. We found COL4A1 expression contributed to the better prognosis in BC patients who received neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…Both processes share some of the cellular mechanisms in cell adhesion, invasion, and angiogenesis (Murray and Lessey, 1999). miRs such as hsa-miR-29c (Griffiths et al, 2019) and hsa-miR-125b (Chen et al, 2016) that are dysregulated in the endometrium from infertile women are also associated with gastric and endometrial cancers (Shang et al, 2012;Wang et al, 2019). Cancer cells releasing miRs into the blood may confound the detection of miRs secreted by the endometrium.…”
Section: Bloodmentioning
confidence: 99%
“…A panel of miRs will likely to be included, with the functional consequence of each individual miR on implantation being confirmed in ideally both humans ( in vitro ) and preclinical animal models ( in vivo ). Detailed functional studies have only covered a small proportion of miRs identified so far ( Table 2 ; Chu et al, 2015 ; Cuman et al, 2015 ; Kang et al, 2015 ; Kottawatta et al, 2015 ; Vilella et al, 2015 ; Zhang et al, 2015 ; Cai et al, 2016 ; Chen et al, 2016 ; Zheng et al, 2017 ; Sirohi et al, 2018 ; Winship et al, 2018 ; Balaguer et al, 2019 ; Griffiths et al, 2019 ; Takamura et al, 2019 ).…”
Section: Spent Blastocyst Culture Mediummentioning
confidence: 99%
“…Several mechanisms can reduce CDH6 expression in the infertile endometrium. microRNA downregulates gene expression [44] and our previous studies reveal that specific microRNAs are increased in the infertile human endometrium and affect endometrial adhesive capacity and receptivity by downregulating essential gene targets [30,31]. CDH6 is a direct gene target of miR-223-3p and forced overexpression of miR-223-3p in cultured osteosarcoma cells reduces CDH6 expression and inhibits cell invasion and migration [45].…”
Section: Discussionmentioning
confidence: 99%
“…Slides were then mounted with DPX and imaged using an Olympus light microscope. Staining intensity scores were determined by two individual scorers blinded to the patient characteristic, as previously described [30]. Briefly, a score of 0 denoted no CDH6 staining and 3 was maximal staining.…”
Section: Immunohistochemistry and Immunocytochemistrymentioning
confidence: 99%